'Full spectrum dominance': Donald Rumsfeld, the Department of Defense, and US irregular warfare strategy 2001-2008 - Ryan, Maria (Routledge, 2014)
This article examines the evolution of US irregular warfare (IW) doctrine and practice from 2001 onwards. It argues that, after 9/11, top-tier civilian policymakers in the US Department of Defense (DoD) and across the US government developed a heightened awareness of asymmetric threats and non-conventional forms of warfare, especially those shaped by contemporary globalisation. The result was a gradual turn towards irregular warfare, led by Rumsfeld and the DoD, designed to ensure ‘full spectrum dominance’ across all modes of conflict. This pre-dated the insurgency in Iraq and the promotion of counterinsurgency in the US Army by General David Petraeus and others. Policymakers' reluctance to acknowledge the insurgency in Iraq was not down to a failure to understand the concept of IW, but because they had viewed Iraq in conventional terms for so many years and were reluctant to admit their mistake.